E-Communication and Customer Satisfaction: a Case of the Mobile Telecommunications Industry in South Africa - Veerasamy, Dayaneethie; Govender, Jeevarathnam Parthasarathy (Journal of Economics and Behavioral Studies, 2017)
Electronic communication (e-communication) refers to communicating by electronic means, especially over computer networks. Organisations use the internet to distribute valuable content in a variety of ways including e-newsletters, articles, videos, webinars, chats, live online events, social networks and forums. Customer satisfaction measures how well the expectations of a customer concerning a product or service provided by an organisation have been met. Customers can be satisfied with more than just the organisation’s product offerings. Customers use the Internet to search for general information, instruction guides or tips that they consider interesting or valuable. They often base their buying decisions on what they find. Valuable content can result in positive advertising as customers share positive content-related experiences with others. It can also increase loyalty as customers start to view or perceive an organisation as an expert about industry-related topics. This paper examines the relationship between e-communication and customer satisfaction within the mobile telecommunications industry in South Africa. This research was quantitative, descriptive and cross sectional in nature. The study found that e-communication was being used by the majority of the service providers in the mobile telecommunications industry and that it led to increased customer satisfaction.